AB1145 Health-Related Quality of Life in the Elderly Suffering Falls: The Influence of Beliefs on Health and the Fear of Falling. (9th June 2015) - Nuñez, E.; Sastre, S.; Lozano, L.; Garcia-Cardό, A.; Salό, S.; Segur, J.M.; Sapena, N.; Segura, V.; Montañana, J.; Alemany, X.; Moreno, J.; Nuñez, M.
Abstract : Background: Falls are an increasing health problem and are more frequent in females. Beliefs and behaviour are known to influence the health status. Objectives: To evaluate the influence of beliefs on health-related quality of life (HRQL) in women aged ≥65 years who had suffered falls in the previous 6 months. Methods: Observational study. Sociodemographic and clinical variables were collected. Beliefs were determined using the Falls Efficacy Scale-International (FES-I), which evaluates the fear of falling, and a question on self-efficacy with respect to health: "Do you believe that your behaviour can influence your health status?" This was measured on a 5-point Likert scale: 1) Totally agree: 2) Quite agree; 3) Don't know; 4) Quite disagree; 5) Totally disagree. HRQL was measured using the SF-36 and WOMAC questionnaires. Gait and balance was evaluated using the Tinetti test. Statistical analysis: Correlations between HRQL and beliefs were calculated. Linear multiple regression was used to evaluate the association between significant independent variables and the physical component of the SF-36 (PC) and the total WOMAC score (TW). Results: 46 women (mean age 75.4 years (SD 6.8), BMI 30.3 (5.7), number of comorbidities 6.1 (SD 2.4), of which 75% were taking ≥4 medications (mean 6.1 [SD 2.4]) were included. Mean Tinetti score was 23.1 points (SD14.6), mean FES-I was 29.9 points (SD 20.6): 69.6% of patients believed their behaviour influenced their health, PC 34.2 points (SD 8.1) and TW 45.3 points (SD 24.7). Significant correlations were found between the fear of falling (FES-I) and HRQL. Correlations were 61% (p<0.001) with the PC, 58% (p<0.001) with the TW, and 45% (p=0.006) with the Tinetti test. Patients who agreed their behaviour could influence their health had significantly better HRQL (TW score [40.4 vs 56.5 p=0.029] and the Tinetti score [23.39 vs 11.36 p=0.002]). Regression analysis showed that 36% of the variability in the PC was explained by the fear of falling. The variability in the TW was explained by the fear of falling (35%) and the BMI (11%). Age, number of comorbidities and number of medications had no influence on the two models. Conclusions: Patients who believed their behaviour influenced their health had a better HRQL and a lower risk of suffering falls than those who did not. Health professionals should take patients' beliefs into account when planning and introducing interventions to prevent falls and improve HRQL. References: World Health Organization. Falls 2012. http://www.who.int/mediacentre/factsheets/fs344/en/ Informe de salud 2013. Generalitat de Catalunya. 2014. Bandura A. Self-efficacy: Toward a Unifying theory of behavioral change. Psychological Rev 1977;84(2):191-215. Acknowledgements: The FATE project has been funded by CIPICT-PSP-2011-5 297178 Disclosure of Interest: None declared